MOTIVASI KERJA GURU DAN KEPEMIMPINAN KEPALA SEKOLAH: SEBUAH SURVEI PADA GURU SEKOLAH MENENGAH PERTAMA SWASTA - Yunita Kwartarani (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
This article aims to analyze the relationship between teacher work motivation and principal's leadership. The research method uses a survey with correlational analysis techniques. A total of 95 private junior high school teachers were used as research samples. Determination of the sample was carried out randomly on teachers at 9 private junior high schools in Cilandak District, South Jakarta. The research instrument used a Likert scale questionnaire with five validated options. Data analysis used simple linear regression to analyze the relationship between the two variables. The results of the research show that there is a strong relationship between the two variables. This finding concludes that there is a strong relationship between teacher work motivation and principal's leadership. Based on these findings, it is suggested that in determining school principals, they should pay attention to the suggestions and inputs of teachers in schools.